2016
DOI: 10.1177/1056789515625451
|View full text |Cite
|
Sign up to set email alerts
|

Application of the equivalent material concept to ductile failure prediction of blunt V-notches encountering moderate-scale yielding

Abstract: The equivalent material concept, proposed originally by the first author for predicting tensile load-carrying capacity of ductile metallic materials weakened by V-notches, was employed together with two well-known brittle fracture criteria, namely the point-stress and the mean-stress criteria, to estimate theoretically the tensile load-carrying capacity of rectangular plates made of Al 7075-T6 and weakened by blunt V-notches encountering moderate-scale yielding at failure. With average discrepancies of 12.4 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…The approach provides accurate predictions in both cases, generally lower than those by FFM, although the maximum percentage discrepancy exceeds 10% for the largest holes. On the other hand, despite not reported here, results by the LM are always very close (indeed a little higher) to the FFM ones described by Equation .…”
Section: Ffm Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The approach provides accurate predictions in both cases, generally lower than those by FFM, although the maximum percentage discrepancy exceeds 10% for the largest holes. On the other hand, despite not reported here, results by the LM are always very close (indeed a little higher) to the FFM ones described by Equation .…”
Section: Ffm Resultssupporting
confidence: 81%
“…FFM approaches have been applied to different geometries, materials, and loading conditions. Some recent applications include, among the others, the failure behaviour of metals even under moderate or large scale yielding, the investigation of three‐dimensional effects, the description of T‐stress effects on the straight and curved crack deflection, and the study of crack nucleation in negative geometries …”
Section: Introductionmentioning
confidence: 99%
“…Torabi proposed the equivalent material concept to deal with ductile mixed‐mode fracture of metallic material. It was found that the equivalent material concept in conjunction with MTS and the mean‐stress criteria could provide satisfactory predictions to the experimental results …”
Section: Introductionmentioning
confidence: 95%
“…It was found that the equivalent material concept in conjunction with MTS and the mean-stress criteria could provide satisfactory predictions to the experimental results. [15][16][17][18] In the experiment aspect, the Arcan specimen and its modified versions have been widely used. 19 The circular sample was first introduced by Arcan et al to test mechanical properties of composites in plane-stress conditions and especially in the pure-shear case.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated tensile strength of the equivalent material ()σf* gives the permission to use brittle fracture criteria for ductile failure predictions. The EMC has been successfully employed in several researches for failure prediction of notched members made of various ductile materials …”
Section: The Equivalent Materials Conceptmentioning
confidence: 99%